2021
DOI: 10.1186/s43141-020-00113-y
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of gold nanoparticles using Argemone mexicana L. and their cytotoxic and genotoxic effects on human colon cancer cell line (HCT-15)

Abstract: Background Nanomedicine has evolved as precision medicine in novel therapeutic approach of cancer management. The present study investigated the efficacy of biogenic gold nanoparticles synthesized using Argemone mexicana L. aqueous extract (AM-AuNPs) against the human colon cancer cell line, HCT-15. Results Biosynthesis of AM-AuNPs was determined by ultraviolet-visible spectroscopy and further characterized by transmission electron microscopy, X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
3
10
0
2
Order By: Relevance
“…It is worth mentioning that the observed differences between our results and the aforementioned studies might be derived from the different nature of AuNPs and the studied cell lines. Aside from inhibitory effects, in the current study and some others [11] , it was observed that morphological changes after treatment with AuNPs would depend remarkably on the concentration adopted from the MTT assay.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…It is worth mentioning that the observed differences between our results and the aforementioned studies might be derived from the different nature of AuNPs and the studied cell lines. Aside from inhibitory effects, in the current study and some others [11] , it was observed that morphological changes after treatment with AuNPs would depend remarkably on the concentration adopted from the MTT assay.…”
Section: Discussionsupporting
confidence: 46%
“…Mechanistically, AuNP-treated cells produce lots of reactive oxygen species (ROS) causing membrane damage, increased mitochondrial activity and eventually cancer cell death. [11] Oxidative stress is often described as a cellular status caused by an increased amount of oxidants (free radicals or reactive species) over antioxidants. It is usually stated in this case that the free radicals destroy the antioxidants defense system.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle altın nanopartiküller kendilerine özgü kimyasal, fiziksel ve nontoksik özellikleri nedeni ile kanser tedavisi ve görüntülemesinde kullanımlarının araştırılması yönünden en yaygın çalışılan nanometallerden biridir. Son yıllarda, altın nanopartiküller basit bir şekilde sentezlenebilmeleri, yüzey modifikasyonlarının yapılabilmesi, ayarlanabilir çekirdek boyutu ve şekline sahip olmaları ve benzersiz optik özellikleri nedeniyle görüntüleme ajanları, teranostik ajanlar ve ilaç taşıyıcı sistemler olarak bilimsel araştırmalarda ilgi odağı haline gelmiştir (27)(28)(29).…”
Section: Discussionunclassified
“…Results show IC50 values of 20.53 μg/mL and 12.03 μg/mL after exposing the cells to biogenic AuNPs for 24 and 48 h, respectively. Increased apoptosis with altered morphology of cells was observed together with overexpressed p53 and caspase-3 [ 173 ].…”
Section: Green Synthesis Of Aunps For Cancer Theranosticsmentioning
confidence: 99%